Factors Related Nurse Retention in Muhammadiyah Hospital Bandung - Yusrina Zata Yumni, Safira; Fajar Hendarman, Achmad (Journal of Business and Management, 2019)
Background: Hospital is a health institution carried out by professional workers including nurse. The presence of nurse to keep working is important to be maintained to provide best services for patients. In several private hospitals in Indonesia, nurse turnover rate is high which have range between 13-35%. Muhammadiyah Hospital Bandung is one of private hospital that has low nurse turnover rate which only 4.82%. Seeing the success of this hospital in applying the practice of retention to nurse, this research want to find out factors that affect to nurse retention in Muhammadiyah Hospital Bandung. Methods: This research distributed some questionnaire to 100 nurses for collecting the data. In analyzing the data it used factor analysis to find out factors that affect to nurse retention. Results: The data has been collected under 20 variables from 100 respondents. The result showed there are five factors that are new formed which have affect to nurse retention. Those factors are supportive environment, leader support, work task, work colleagues, and feeling involved. Conclusion: Based on these findings, those five factors that have affect with nurse retention in Muhammadiyah Hospital Bandung. Keywords: Factor Analysis, Muhammadiyah Hospital Bandung, Nurse, Retention